Subjective Sleep Quality in Amnestic Mild Cognitive Impairment Elderly and Its Possible Relationship With Plasma Amyloid-β - Liu, Yajing; Chen, Lushi; Huang, Shuyun; Zhang, Chengguo; Lv, Zeping; Luo, Jiali; Shang, Pan; Wang, Yukai; Xie, Haiqun (Frontiers in Neuroscience, 2020)
Study objectives To investigate the extent to which sleep quality associated with plasma Aβ levels in amnestic mild cognitive impairment (aMCI) elderly. Methods A total of 172 cognitively normal (NC) elderly and 133 aMCI elderly were included in this study. For the evaluation of sleep quality, the Pittsburgh Sleep Quality Index (PSQI) was used. Levels of plasma Aβ were determined by the sandwich enzyme-linked immunosorbent assay technique. Multivariable linear regression analysis was applied to evaluate associations between sleep quality and plasma Aβ levels after adjusting potential confounders. Results Compared to NC subjects, participants with aMCI had a higher global PSQI score (8.72 ± 3.87 vs. 7.10 ± 3.07, p < 0.001). The global PSQI score was positively associated with plasma Aβ42 level in the aMCI group (β = 0.063, 95% CI 0.001–0.125, and p = 0.049) but not in the NC group (p > 0.05). Additionally, a higher global PSQI score was associated with a higher plasma Aβ42/Aβ40 ratio in both NC (β = 0.010, 95% CI 0.003–0.016, and p = 0.003) and aMCI groups (β = 0.012, 95% CI 0.005–0.018, and p < 0.001). The association between global PSQI score and plasma Aβ42/Aβ40 ratio was stronger in individuals with aMCI relative to the NC subjects (β = 0.076 vs. 0.030, p for interaction = 0.023). Conclusion Poor sleep quality was associated with plasma Aβ42 and Aβ42/Aβ40 ratio, with a stronger effect among individuals with aMCI. A better understanding of the role of sleep in plasma Aβ levels in aMCI patients could lead to effective sleep-based intervention against the risk of Alzheimer’s disease.